The field of eurocracy mapping eu actors and professionals - Georgakakis, Didier; Rowell, Jay.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The word Eurocracy has resonance throughout out Europe but in reality we know little about the people who work in and around the EU or how they fit into its large bureaucratic framework. Based on extensive fieldwork, this book addresses this problem by exploring the MEPs, diplomats, civil servants and commissioners that work in and around the EU.
Keywords: Political science; Public policy; European Union; Globalization; Public administration; Political sociology; Political Science and International Relations; European Union Politics; Political Sociology; Political Science; Public Policy; Public Administration; Globalization